ANALISIS INVESMENT CAPITAL OUTPUT RATIO (ICOR) DALAM RANGKA PROYEKSI KEBUTUHAN INVESTASI DI KABUPATEN MAJALENGKA TAHUN 2017-2019 - L. Suparto LM (MAKSI, 2017)
Success of the region to enhance the competitiveness of the investment one of whichdepend on the ability of the region to formulate policies relating to investment andbusiness, as well as improving the quality of service to the community. It is also importantto consider in an effort to attract investors, in addition to conducive macroeconomic alsotheir human resource development and infrastructure in the broadest sense. This conditionwill be able to mobilize the private sector to participate in moving the economic wheel.This study aims to determine the value of the coefficient ICOR and the projectedinvestment needs in Majalengka during the years 2017-2019. The data used is secondarydata, Gross Domestic Product, the consumer price index, and the economic growth rate.Analysis data using the formula coefficient ICOR and the projected investment needsdeveloped by Widodo. The analysis showed that the coefficient ICOR Majalengka duringthe years 2011-2014 shows a positive development, which meaning that the productivity ofcapital formation in Majalengka increased in order to encourage the rise of regionaleconomic growth and the projected investment needs in Majalengka in 2017-2019 , tendvolatif. But the need for investment in 2019 is increasing. Key Word : Economic Growth, ICOR and Invesment